Ekspektasi Orang Tua Terhadap Anak Perspektif Tafsir Virtual: Kajian Akun Instagram @quranreview - Pelu, Nadhlif; Firdaus, Nadya Fitri (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2025)
These day, parents’ expectations of their children often draw scrutiny from various quarters. This is because some of these expectations contain realistic demands and others tend to be unrealistic. In the Qur’an, parents’ expectations of their children are not expessed, but are prayed for through prayer. These expectations tend to lead to parents’ good wishes for their children in the afterlife. If we look at the context of life today, the reality is much different. The majority of today’s parents have high expectations of their children and even verbalize them. This will certainly burden the psychological and academic conditions of children. The purpose of this research is to analyze parents’ expectations of their children from perspective of the science of the Qur’an and tafseer, and how the concept is presented in the content of the @quranreview Instagram account. This research is qualitative and use content analysis. The results show that there is significant difference between the expectations of parents as stated in the Qur’an and the current social reality. Parents’ expectations through the Qur’anic approach prioritize prayer nd sincerity. But when viewed through a modern social approach, these expectations often contain unrealistic burdens, so that the child gets inner pressure in meeting these high expectations